(untitled) (Journal of the College of Basic Education, 2022)
Paradox is the difference, separation, separation, divergence, contrast, and distinction between two things, two things, or two situations... especially if these two things are on opposite sides, or one of them is contrary to the other, or the opposite of it... Perhaps this meaning remains monolithic, unless it is synonymous with paradox in the idiomatic sense until it is straight. Both sides of the equation - that is, the paradox from both angles of observation.By limiting the meanings, connotations, and concepts, old and new, to the idiomatic meaning of paradox, we reach that it is ((a high-tech rhetorical style, based on presenting two equal, opposing viewpoints, between a common general concept and another subjective intellectual one, and the more intense the contradiction between them, the paradox emerges.